Psikoedukasi Untuk Meningkatkan Pemahaman Tentang Bahaya Napza Pada Pasien Rehabilitasi Napza - Ambiya, Wina Al; Anniez Rachmawati Musslifah (Pusat Riset dan Inovasi Nasional, 2026)
The problem of narcotics, psychotropic, and addictive substances (NAPZA) abuse has a wide negative impact on the physical, psychological, and social aspects of patients. Rehabilitation efforts not only emphasize physical recovery, but also require innovative psychoeducation to support behavioral changes and increased knowledge. This study aims to evaluate the effectiveness of creative psychoeducation based on games show recovery as an educational medium and cognitive stimulation in the rehabilitation process of NAPZA patients. The method used is a literature study and descriptive analysis of the implementation of the educational game